Spontaneous mapping of number and space in adults and young children - de Hevia, Maria Dolores (2008)
Mature representations of space and number are connected to one another in ways suggestive of a ‘mental number line’, but this mapping could either be a cultural construction or a reflection of a more fundamental link between the domains of number and geometry. Using a manual bisection paradigm, we tested for number line representations in adults, young school children, and preschool children. Non-symbolic numerical displays systematically distorted localization of the midpoint of a horizontal line at all three ages. Numerical and spatial representations therefore are linked prior to the onset of formal instruction, in a manner that suggests a privileged relation between spatial and numerical cognition.